EFFECT OF E-SERVICE QUALITY, PRODUCT COMPLETENESS AND PROMOTION ON CONSUMER'S REPURCHASING INTEREST (MATAHARI.COM CASE STUDY) - Dadar Supriatna (Jurnal Ekonomi, 2022)
This study aims to determine: (1) e-service quality, product completeness and promotion on consumer repurchase interest (the Matahari.com case study) (2) the effect of e-service quality, product completeness and promotion on consumer repurchase interest (study of the case of Matahari.com) partially and (3) the effect of e-service quality, product completeness and promotion on consumer repurchase interest (the case study of Matahari.com) simultaneously.The population in this study are consumers who have visited the website and application on Matahari.com in the city of Bandung. The sampling technique used the Structural Equation Model (SEM) analysis method with a total sample of 140 people. The data analysis technique used is multiple regression. The results showed that: (1) there was a positive effect of e-service quality on consumer repurchase interest (the case study of Matahari.com), as evidenced by the t-count value of 2.120, (2) there was a positive effect of product completeness on consumer repurchase interest ( the case study of Matahari.com), as evidenced by the t-count value of 2.201, (3) there is a positive effect of promotion on consumer repurchase interest (the case study of Matahari.com). evidenced from the t-count value of 4.059 and (4) there is an effect of e-service quality, product completeness and promotion together on consumer repurchase interest (the Matahari.com case study), as evidenced by the calculated F value of 13,841. The results showed that e-service quality, product completeness, promotion and consumer repurchase interest at Matahari.com have values that fall into the "Satisfied" category.